Determinação do custo médio ponderado de capital regulatório para distribuidoras de gás natural - Villela, João Paulo Mesquita (2018)
The objective of this work is to propose a methodology for determining the weighted average cost of capital to be employed by the regulatory agency in the tariff review process of natural gas distributors in the state of São Paulo. The challenge in this process is to establish a remuneration that guarantees the lowest cost with the greatest benefit to the customers and at the same time provides the maintenance of the economic balance and the incentive to expand the services provided by the concessionaires. The complexity of the study becomes evident when we verify the great dispersion of values proposed in the contributions sent to the Sanitation and Energy Regulatory Agency of the State of São Paulo (ARSESP) during the public consultation process. In this sense, the different approaches used by other regulatory agencies also make it difficult to establish a standardized solution to the problem. In this way, we analyzed initially the methodology defined by the ARSESP, the contributions received during the public consultation process carried out by the agency and some references of national and international regulatory practices. Finally, we sought to solve the issue by proposing a methodology considered adequate to estimate the weighted average cost of capital for the natural gas distributors in the state of São Paulo.